A Model-based Approach for Analyzing the Autonomy Levels for Cyber-Physical Systems-of-Systems - Gharib, Mohamad; Silva, Leandro Dias; Kavalionak, Hanna; Ceccarelli, Andrea (Anais do Latin-American Symposium on Dependable Computing (LADC); 2018: Anais do VIII Latin-American Symposium on Dependable Computing, 2018)
A Cyber-Physical System-of-Systems (CPSoS) can be defined as a System-of-Systems (SoS), where its Constituent Systems (CSs) are Cyber-Physical Systems (CPSs). A main challenge in integrating CPSoS to function as a single integrated system is the autonomy of its components, which may result in conflicts due to the lack of coordination among its CPSs. In this paper, we advocate that in order to facilitate the integration of CPSs within the overall context of their CPSoS, we may need to adjust their level of autonomy in a way that enables them to coordinate their activities to avoid any conflict among one another. Reducing such conflicts surely contributes to the dependability of the CPSoS. In particular, we propose a novel model-based approach for modeling and analyzing the autonomy levels of CPSs based on their awareness concerning their operational environment as well as their capability to safely perform their activity. We illustrate the utility of the approach with an example concerning a cooperative driver overtaking assistance system.